2007
DOI: 10.1126/science.1146426
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation Elicits Coupled Neural and Hemodynamic Consequences

Abstract: Transcranial magnetic stimulation (TMS) is an increasingly common technique used to selectively modify neural processing. However, application of TMS is limited by uncertainty concerning its physiological effects. We applied TMS to the cat visual cortex and evaluated the neural and hemodynamic consequences. Short TMS pulse trains elicited initial activation (approximately 1 minute) and prolonged suppression (5 to 10 minutes) of neural responses. Furthermore, TMS disrupted the temporal structure of activity by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
204
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(235 citation statements)
references
References 31 publications
22
204
2
6
Order By: Relevance
“…These results highlight the important possibility that different protocols of TMS are likely to affect neurons in a different fashion. While online TMS induces firing in a subset of the neurons in the stimulated area that interferes with signal processing (Allen et al 2007), offline cTBS is likely to lead to a lowered excitability of the stimulated area (Allen et al 2007;Huang et al 2005). Thus it is perhaps not surprising that online TMS and offline cTBS affect the perceptual system in a different fashion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results highlight the important possibility that different protocols of TMS are likely to affect neurons in a different fashion. While online TMS induces firing in a subset of the neurons in the stimulated area that interferes with signal processing (Allen et al 2007), offline cTBS is likely to lead to a lowered excitability of the stimulated area (Allen et al 2007;Huang et al 2005). Thus it is perhaps not surprising that online TMS and offline cTBS affect the perceptual system in a different fashion.…”
Section: Discussionmentioning
confidence: 99%
“…One recently developed variant of repetitive transcranial magnetic stimulation (TMS), continuous theta burst stimulation (cTBS;Huang et al 2005), has shown promise because of its rapid application (Ͻ1 min), its ability to produce behavioral effects for up to 1 h after stimulation, and its connection to known neuronal mechanisms, such as long-term potentiation and depression (LTD). Indeed, research has shown that cTBS reduces motor cortical excitability in a manner consistent with LTD effects (Allen et al 2007;Di Lazzaro et al 2005Gentner et al 2008;Huang et al 2005Huang et al , 2007.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TMS is a means of using electromagnetic induction in order to stimulate a brain region. Repetitive delivery of TMS pulses (rTMS) to a brain region modulates the excitability of the stimulated area, inducing changes in neural plasticity (Allen, Pasley, Duong, & Freeman, 2007). These neuroplastic changes outlast the duration of stimulation and are believed to be induced through long‐term potentiation/depression mechanisms (Esser et al, 2006; Ishikawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, TMS has proved a valuable tool in basic brain research as its perturbative effects allow area-selective manipulation of immediate cortical function (9)(10)(11), as well as its long-lasting alteration through plasticity and learning protocols (12,13). However, direct measurements of the TMS-induced cortical dynamics at highly resolved spatiotemporal scales are missing because "online approaches" (14), using modern neuroimaging techniques such as functional MRI (fMRI) (15)(16)(17)(18), magnetoencephalography (19), EEG (20), and near-infrared (21) or intrinsic optical imaging (22), are limited in either spatial or temporal resolutions or in both.…”
mentioning
confidence: 99%